2019
DOI: 10.1155/2019/7564232
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Compound Sophora on Fluorouracil and Oxaliplatin Resistance in Colorectal Cancer Cells

Abstract: Fluorouracil (5-FU) and oxaliplatin (L-OHP) are the most commonly used chemotherapy drugs for colorectal cancer, though resistance is common. Compound Sophora injection is a traditional Chinese medicine that can protect the liver against oxidation, improve immunity, and enhance sensitivity to chemotherapy; it may have an effect of reversing resistance in 5-FU- and L-OHP-resistant gastric cancer cells (5-FU/SW480 and L-OHP/SW480, respectively). A concentration gradient experiment was performed to identify a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Overexpression of ABC proteins, however, presents an unfavorable implication on the prognosis of colon cancer patients receiving 5-FU treatment with studies reporting both negative and positive correlations [ 20 , 21 , 22 , 23 ]. Nonetheless, incidence of 5-FU resistance is still consistently motivated by elevated levels of ABC transporters, that includes ABCB1 [P-glycoprotein (P-gp) or MDR1] [ 24 , 25 ]; ABCG2 [breast cancer resistance protein (BCRP)] [ 26 , 27 ]; ABCC1 [multidrug resistance-associated protein (MRP1)] [ 28 , 29 ]; ABCC3 [ 20 ], and ABCC2 [ 30 ]. Surprisingly, in one study, 5-FU resistance in colon cancer cells was instead attributed to the loss of ABCB4 [ 31 ].…”
Section: Classical Mechanisms Of Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of ABC proteins, however, presents an unfavorable implication on the prognosis of colon cancer patients receiving 5-FU treatment with studies reporting both negative and positive correlations [ 20 , 21 , 22 , 23 ]. Nonetheless, incidence of 5-FU resistance is still consistently motivated by elevated levels of ABC transporters, that includes ABCB1 [P-glycoprotein (P-gp) or MDR1] [ 24 , 25 ]; ABCG2 [breast cancer resistance protein (BCRP)] [ 26 , 27 ]; ABCC1 [multidrug resistance-associated protein (MRP1)] [ 28 , 29 ]; ABCC3 [ 20 ], and ABCC2 [ 30 ]. Surprisingly, in one study, 5-FU resistance in colon cancer cells was instead attributed to the loss of ABCB4 [ 31 ].…”
Section: Classical Mechanisms Of Resistancementioning
confidence: 99%
“…5-FU-resistant cells typically exhibit attenuated effects of 5-FU cytotoxicity with a higher population of cells detected in both G 1 /S and S phases when compared to 5-FU-susceptible cells [ 27 , 28 , 65 , 66 ]. When DNA synthesis remains unimpaired, 5-FU-resistant cells may also observe a higher population of G 2 phase cells when compared to 5-FU-susceptible cells [ 26 ]. Prolonged G 1 and S phases may provide sufficient time for tumor cells to counteract against 5-FU-induced DNA damage through activation of DNA repair pathways.…”
Section: Classical Mechanisms Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Historically, cancers that spread within the peritoneal cavity were deemed fatal [ 1 , 2 , 3 ]. Colorectal cancer (CRC), also known as bowel, colon, or rectal cancer, is the development of cancer in the large intestine originating from the colon or rectum.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was reported that ginsenoside Re (GRe) had an antineuroinflammation effect in addition to a protective effect against colitis (Lee et al 2012;Zhang et al 2016). Natural compounds in Kampo medicines attract attention as therapeutic agents for diseases with high efficacy and low toxicity (Khan et al 2019;Yin et al 2019).…”
mentioning
confidence: 99%